Textiles and clothing : environmental concerns and solutions - Shabbir, Mohd (Chemist) (John Wiley & Sons, Inc. ; Scrivener Publishing, LLC, 2019)
"All environmental aspects relating to the textile and clothing industry are discussed in this book."
Keywords: Textile industry -- Waste disposal.; Textile industry -- Environmental aspects.; Textile chemicals -- Environmental aspects.; Dyes and dyeing -- Environmental aspects.; Textile fabrics.; Factory and trade waste -- Environmental aspects.; Heavy metals -- Environmental aspects.; elektronické knihy; electronic books